arabic - Wahyu Ramadhan; Lailatul Qomariyah (Program Studi Pendidikan Bahasa Arab, 2024)
: This research aims to determine the effectiveness of using the Mind Mapping Method on the Nahwu Learning Motivation of Class X Students of Madrasah Aliyah Ghozaliyah Jogoroto Jombang. The research method used is quantitative research and the design used is pre-experimental using a One-Group Pretest-Posttest Design research design. The data collection techniques used were interviews, questionnaires and documentation. The results of this research are: 1) Student learning motivation before applying the Mind Mapping method to class X Madarasah Aliyah Jogoroto Jombang students, at this stage it was tested on class that can be seen in the experimental class during the pretest or before being given the mean value of 59.30, median value of 59.50, mode value of 60, standard deviation value of 9.609, minimum value of 40, maximum value of 80. In student learning motivation before implementation, student learning motivation still seemed lacking. 2) Students' learning motivation after applying the Mind Mapping method can be seen in the experimental class during the posttest or after being given the application. The mean value is 65.55, the median value is 63.00, the mode value is 63, the standard deviation value is 11.180, the minimum value is 44, the maximum value is 96. Based on the explanation above, students' learning motivation after applying the Mind Mapping method got very good results. 3) The influence of the mind mapping method on student learning motivation is proven by the acquisition of a pretest questionnaire significance value of . It can be seen that the t-count is more than the t-table, namely, 27,600 > 2.144787 with a df of 19. And the significance is .000 < 0.05 while one posttest sample test can be seen that the t-count is more than the t-table, namely, 26,220 > 2.144787 with df 19. And the significance is .000 < 0.05. Thus, it can be concluded that Ha is accepted and Ho is rejected, which means that the Mind Mapping method has an influence on students' learning motivation in the Nahwu subject I'rab material in class X at Madrasah Aliyah Ghozaliyah Jogoroto Jombang.